PP.08.22: IN YOUNG AND MIDDLE-AGED HYPERTENSIVES THE AUGMENTATION INDEX DEPENDS MORE ON LEFT VENTRICULAR PERFORMANCE THAN REFLECTED WAVE. (June 2015) - Krzesinski, P.; Stanczyk, A.; Gielerak, G.; Kurpaska, M.
Abstract : Objective: Augmentation index (AI) is a well recognized marker of arterial stiffness related to cardiovascular morbidity and mortality. The arterial pulse waveform is the sum of the forward wave generated by left ventricle (LV) and a backward wave reflected from the periphery. The aim of this study was to estimate the relation of AI with hemodynamic indices of LV performance and afterload assessed by impedance cardiography (ICG) in young and middle-aged patients with arterial hypertension (AH). Design and method: This study involved 144 patients (mean age: 45.2 years) with untreated AH. Augmentation index was evaluated by applanation tonometry (SphygmoCor® system) and systolic blood pressure (SBP), diastolic blood pressure (DBP), heart rate (HR), stroke index (SI), cardiac index (CI), Heather index (HI), left ventricular ejection time (LVET), systemic vascular resistance index (SVRI), total artery compliance (TAC) by ICG (Niccomo™ device). The analysis included: interquartile comparison in subgroups of AI < 15% (Q1), 15–22% (Q2), 23–29% (Q3), equal or higher than 30% (Q4) and the assessment of correlation between AI and the above ICG variables. Results: The mean AI in the study group was 21.8 ± 13.3%. Gender distribution among quartiles was disproportionate: lower quartile was dominated by men (97.2%) and upper (Q4) - by women (77.6%; p < 0.00001). The subjects in Q4, in comparison with Q1, were older (41.8 vs 39.8 years; p < 0.00001) and characterized with lower height (166.5 vs 180.8 cm; p < 0.00001), HR (68.1 vs 78.8 bpm; p < 0.00001), longer LVET (330.8 vs 287.7 ms; p < 0.00001), higher SI (52.3 vs 45.5 ml/m 2 ; p < 0.05) and HI (14.8 vs 12.1 Ohm*s 2 ; p < 0.05). No significant differences in DBP, CI, SVRI and TAC were identified. Correlation analysis revealed significant associations of AI with age (r = 0.45; p < 0.00001), height (r = -0.53; p < 0.00001); HR (r = −0.37; p < 0.00001); SI (r = 0.28; p < 0.05), LVET (0.43, p < 0.00001) and HI (r = 0.25; p < 0.001). However, in multivariate linear regression analysis the only independent determinants of AI (as dependent variable) were age, height and HR (R 2 = 0.57). Conclusions: Our results suggest that the strongest determinants of AI in young and middle-aged hypertensives are age, gender, height and hemodynamic indices of LV performance but not those characterised afterload.